The relationship between service quality and tourists' satisfaction at Malacca River Cruise / Maria Albert Panie , Nur Liyana Abdul Rahman and Tracy Alasta Saweng @ Suki - Maria Albert Panie; Nur Liyana Abdul Rahman; Tracy Alasta Saweng @ Suki (Faculty of Hotel and Tourism Management, 2014)
This research is to evaluate the relationship between service quality provided at Malacca River Cruise towards satisfaction among International tourists'. In this research, there are five dimensions to measure the tourist satisfaction. Therefore, this study find that there are five service quality dimensions that are used to measure the satisfaction level such as tangible, reliability, responsiveness, assurance, and empathy. After that, this research also will focus on two (2) objectives which are; to determine the positive relationship between service quality dimensions and International tourist's satisfaction and to identify the most agreeable dimension in service quality that influence tourists' satisfaction. As the result, the findings of the study is significant with the objectives stated. These result will be discuss in the finding of the study. At the end of the research, the limitation that becomes constraint to this research will be discussed. Furthermore, the researcher also will include some recommendations to future researcher to improve more in their research. Besides, conclusion will be stated to discuss and conclude about all the information in this research.